Exact Controllability for a Class of Nonlinear Evolution Control Systems (Communications in Mathematical Research, 2021)
In this paper, we study the exact controllability of the nonlinear controlsystems. The controllability results by using the monotone operator theory are established. No compactness assumptions are imposed in the main results.